Perlindungan Hukum Terhadap Nasabah Dalam Praktik Pembiayaan Murabahah Pada Lembaga Keuangan Syariah Di Indonesia - Nurbaitillah; Nasaruddin; Ramadoni; Robi Darwis; Fuad; Iksan (Muhammadiyah University of Surabaya, 2025)
This article attempts to uncover and analyze the problematic legal protection for customers in the implementation of murabahah financing contracts by Islamic financial institutions in Indonesia. Although the murabahah contract is normatively one of the main instruments in the Islamic financing system based on the principles of openness and justice, empirical reality shows that there is still an imbalance in the legal relationship between customers and Islamic financial institutions. This imbalance is reflected in the application of unilateral standard clauses, disproportionate collateral execution mechanisms, and minimal transparency regarding cost components and profit margins in the financing structure. Therefore, the main objective of this study is to examine in depth the form of legal protection for customers in murabahah practices, while at the same time assessing its compliance with the principles of justice, balance, and transparency as mandated in national laws and regulations and Islamic legal principles. This study uses a normative legal approach with a descriptive analysis method that examines positive legal norms, including Law Number 21 of 2008 concerning Islamic Banking, Law Number 8 of 1999 concerning Consumer Protection, and the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as a reference for substantive law. The findings indicate a legal vacuum and implementation weaknesses in the aspect of protecting customer rights, especially regarding the position of customers as the weak party in contractual relations. This article offers an update in the form of an ideal model formulation of legal protection based on integration between Islamic law and the national legal system, in order to ensure normative balance and legal certainty for all parties involved. Thus, this article is expected to provide theoretical and practical contributions in strengthening the Islamic economic legal system that is oriented towards justice and welfare. Keywords: Legal Protection, Sharia Banking Customers, Sharia Financial Institutions, Legal Certainty in Contracts